2008
DOI: 10.1007/s10096-008-0681-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii oocysts in environmental soil samples using molecular methods

Abstract: Infections caused by Toxoplasma gondii are prevalent in humans and animals throughout the world. So far, there is no sufficient information concerning T. gondii oocysts prevalence in the environment, especially in soil. Therefore, the aim of this study was to estimate occurrence of T. gondii oocysts in soil and determine the genotype of detected parasites. A total of 101 soil samples were taken from different sites (sand-pits, "farming ground", areas around rubbish dumps) located in the Tri-City (Poland). Oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…A study of a cat population living in the Croix-Rousse hospital (Lyon, France) showed that defecation sites were the areas most often found to be positive for T. gondii DNA, and may be viewed as hot spots of environmental risk to humans [50]. Similarly, in Poland and in China, contaminated soil samples have been found in public parks and sand pits [67,68]. Contact with soil, and particularly gardening and consumption of raw vegetables have been demonstrated to be significant risk factors for toxoplasmosis in humans [69,7,70].…”
Section: Urban Toxoplasmosismentioning
confidence: 99%
See 1 more Smart Citation
“…A study of a cat population living in the Croix-Rousse hospital (Lyon, France) showed that defecation sites were the areas most often found to be positive for T. gondii DNA, and may be viewed as hot spots of environmental risk to humans [50]. Similarly, in Poland and in China, contaminated soil samples have been found in public parks and sand pits [67,68]. Contact with soil, and particularly gardening and consumption of raw vegetables have been demonstrated to be significant risk factors for toxoplasmosis in humans [69,7,70].…”
Section: Urban Toxoplasmosismentioning
confidence: 99%
“…Contact with defecation sites is thus expected to result in a high risk of infection, but, because contaminated sites represent a low proportion of the area, only a few humans are likely to be directly exposed. These persons include children playing in sand pits, persons feeding the cats, gardeners, maintenance workers in these sites and also dog owners who allow pets to roam in these sites and become indirectly exposed through contact with dogs [71,67,68].…”
Section: Urban Toxoplasmosismentioning
confidence: 99%
“…Then the mixtures were sonicated to produce a smooth dispersion and the desired concentration was prepared daily in physiological saline and administered to mice at a dosage of 250 mg/kg/day, according to the animal's body weight, for 5 or 10 days, 24 h after infection.…”
Section: Drugsmentioning
confidence: 99%
“…Other members of the same phylum, Apicomplexa, include the human pathogens Plasmodium and Cryptosporidium, and the animal pathogens Eimeria and Sarcocystis [3][4][5] . T. gondii has become a model organism for the study of the Apicomplexa, as it is the most experimentally tractable organism in this important group of intracellular parasites that includes Plasmodium, Eimeria, Cryptosporidium, Neospora, and Theileria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation